Risk of thrombosis and bleeding in gynecologic cancer surgery: systematic review and meta-analysis - Lavikainen Lauri I.; Guyatt Gordon H.; Luomaranta Anna L.; Cartwright Rufus; Kalliala Ilkka E.J.; Couban Rachel J.; Aaltonen Riikka L.; Aro Karoliina M.; Cárdenas Jovita L.; Devereaux P.J.; Galambosi Päivi J.; Ge Fang Zhou; et al. (Elsevier Inc., 2025)
Objective: This study aimed to provide procedure-specific estimates of the risk of symptomatic venous thromboembolism and major bleeding in the absence of thromboprophylaxis, following gynecologic cancer surgery.
Data sources: We conducted comprehensive searches on Embase, MEDLINE, Web of Science, and Google Scholar for observational studies. We also reviewed reference lists of eligible studies and review articles. We performed separate searches for randomized trials addressing effects of thromboprophylaxis and conducted a web-based survey on thromboprophylaxis practice.
Study eligibility criteria: Observational studies enrolling ≥50 adult patients undergoing gynecologic cancer surgery procedures reporting absolute incidence for at least 1 of the following were included: symptomatic pulmonary embolism, symptomatic deep vein thrombosis, symptomatic venous thromboembolism, bleeding requiring reintervention (including reexploration and angioembolization), bleeding leading to transfusion, or postoperative hemoglobin <70 g/L.
Methods: Two reviewers independently assessed eligibility, performed data extraction, and evaluated risk of bias of eligible articles. We adjusted the reported estimates for thromboprophylaxis and length of follow-up and used the median value from studies to determine cumulative incidence at 4 weeks postsurgery stratified by patient venous thromboembolism risk factors. The GRADE approach was applied to rate evidence certainty.
Results: We included 188 studies (398,167 patients) reporting on 37 gynecologic cancer surgery procedures. The evidence certainty was generally low to very low. Median symptomatic venous thromboembolism risk (in the absence of prophylaxis) was <1% in 13 of 37 (35%) procedures, 1% to 2% in 11 of 37 (30%), and >2.0% in 13 of 37 (35%). The risks of venous thromboembolism varied from 0.1% in low venous thromboembolism risk patients undergoing cervical conization to 33.5% in high venous thromboembolism risk patients undergoing pelvic exenteration. Estimates of bleeding requiring reintervention varied from <0.1% to 1.3%. Median risks of bleeding requiring reintervention were <1% in 22 of 29 (76%) and 1% to 2% in 7 of 29 (24%) procedures.
Conclusion: Venous thromboembolism reduction with thromboprophylaxis likely outweighs the increase in bleeding requiring reintervention in many gynecologic cancer procedures (eg, open surgery for ovarian cancer and pelvic exenteration). In some procedures (eg, laparoscopic total hysterectomy without lymphadenectomy), thromboembolism and bleeding risks are similar, and decisions depend on individual risk prediction and values and preferences regarding venous thromboembolism and bleeding.